A review of the genus Syrianarpia Leraut (Crambidae: Scopariinae) with description of S. elburzalis sp. n. from Iran - Alipanah, Helen; Gianti, Mauro (Zootaxa, 2017)
Syrianarpia elburzalis sp. n. (Crambidae: Scopariinae) is described as a new species from Iran. A taxonomic review of the genus and an identification key to the known species are provided. New data on morphology, genitalia, distribution, and habitat of the studied Iranian species are provided.